The Legal Politics of State Losses (Study of Verdict Number: 116/Pid.Sus-Tpk/2014/Pn.Smg) - Adissya Mega Christia; Anggit Wicaksono (International Journal Labs, 2023)
State losses are caused by unlawful acts due to intent or negligence. State losses greatly affect state finances. Law Number 17 Year 2003 concerning State Finance and Law Number 1 Year 2004 concerning the State Treasury and various related regulations should be the legal basis for interpreting unlawful acts that result in state losses. This research is a study of Decision Number: 116/Pid.Sus-TPK/2014/PN.Smg because in the decision there are several things that are not in accordance with the laws and regulations in the field of state finance, especially in terms of state losses. This study uses a normative juridical method with a case approach, a statutory approach, and a conceptual approach. From this study it can be concluded that the determination of state losses should be based on the results of the KPK audit, the determination of cooperation agreements for the procurement of goods must be in accordance with the fiscal year, and there must be a clear legal basis regarding accountability for managing state finances.